Acciones afirmativas en la educación superior y en la movilidad social: Un estudio de campo - Silva, Luís Felipe Oliveira Alves da; Ferreira, André; Teodoro Lacerda, Pítias; Silva, Yury Vasconcellos da (Universidad de Costa Rica, 2022)
The quota policy in Brazilian public universities, implemented in 2012, which facilitated the access of the less favored classes to higher education in the country, is expected to be revised in the year 2022. Aiming to generate subsidies for this debate, this article has as aim to investigate the influence of this public policy on the social mobility of beneficiaries. For this, a comparative study was carried out between the graduates of the quotas and general competition groups. This paper is applied research with a quantitative approach. Data collection was carried out from September to October 2020, through a questionnaire sent by email to 541 graduates from undergraduate courses offered by Universidade Federal Fluminense in the city of Volta Redonda-RJ. The survey obtained 77 valid responses (14.2% of the total), with 54 entering the university due to wide competition and 23 through quota groups. For data analysis, descriptive and inferential statistics were used. In the scope of this sample, the main results indicate that the graduates of the studied groups have their own characteristics: the group of graduates who entered university through the quota system started their life in the labor market before, has a higher percentage of people who expect to social mobility and, among the alumni who expect social mobility, those who are part of the quota group expect to ascend a greater number of social levels than the alumni with broad competition.